Inégalités de genre en entreprise : comment construire une intervention sur le travail, propice aux transformations ? - Laurence Théry; Florence Chappert (Perspectives Interdisciplinaires sur le Travail et la Santé)
Some health problems at work, increased by ever more intense work demands, result in absenteeism, turnover, stress, work exhaustion, and MSDs. These problems are treated with more appropriate preventive measures when ergonomic interventions take into account the differences between the work situations of women and men. It is through data analysis (population, health, human resources) and work analysis that the intervention can objectify these differences and encourage their discussion in the company. Four causal factors have been identified : the sexual division of labor, the invisibility of risks and of work strenuousness in female-dominated sectors, differences in occupational paths, and differing exposures to time constraints in occupational and domestic work. This type of interpretation makes it easier for changes to occur in companies. That being said, interventions in companies encounter resistance insofar as these differences reflect gender inequalities between women and men resulting from social dynamics that are still difficult to address.